2006
DOI: 10.1007/s12043-006-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

Control of amplification without inversion in H2 and LiH molecules: Dependence on relative magnitude of probe and coherent field Rabi frequencies in three-level Λ system

Abstract: Dependence of amplification without inversion (AWI) on the relative strength of probe and coherent field Rabi frequencies has been studied in H 2 and LiH molecules for three-level Λ configuration. We have derived exact analytical expressions for coherences and populations keeping all the orders of probe field Rabi frequency (G) and coherent field Rabi frequency (Ω) in the steady state limit. Previously, first-order approximation (i.e. keeping only the first-order term in G) was used and hence AWI was studied f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Thus, the system with upper state A 1 + (v = 0, j = 2) and the lower dressed states |+ , |− behaves as a system with antiparallel dipole moments. The spontaneous decay widths (γ + and γ − ) can be calculated from dipole transition moments (d 2+ and d 2− ) and frequencies of transition [49][50][51]. This system has the advantage that the magnitudes of the dipole transition moments (d 2+ and d 2− ) and the energy separation between dressed states (S ) can be controlled by the Rabi frequency (S) and detuning of the driving laser field ( L ).…”
Section: Realization Of Sgc In Heteronuclear Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the system with upper state A 1 + (v = 0, j = 2) and the lower dressed states |+ , |− behaves as a system with antiparallel dipole moments. The spontaneous decay widths (γ + and γ − ) can be calculated from dipole transition moments (d 2+ and d 2− ) and frequencies of transition [49][50][51]. This system has the advantage that the magnitudes of the dipole transition moments (d 2+ and d 2− ) and the energy separation between dressed states (S ) can be controlled by the Rabi frequency (S) and detuning of the driving laser field ( L ).…”
Section: Realization Of Sgc In Heteronuclear Moleculesmentioning
confidence: 99%
“…In this paper, we show theoretically the effect of both SGC [19,20,46,47] and DIC [48][49][50][51] on the susceptibility and the group index of a closed three-level system in the presence of incoherent pumping. In a three-level system two of the levels are coupled by a coherent field and the probe field is applied between one of these two levels and a third level (i.e., ground state or a lower level).…”
Section: Introductionmentioning
confidence: 97%
“…As mentioned before the spacing between two dressed levels (|+ and |− ) can be adjusted to be greater than the homogeneous/inhomogeneous width (by controlling S and ∆ L ). Usually in small molecules the homogeneous width becomes three orders of magnitude greater than the individual spontaneous decay width [23,34]. Here the individual spontaneous decay widths are on the order of ≈ 10 −13 a.u.…”
mentioning
confidence: 97%
“…It is well known that the dephasing due to the decay to other vibrational levels can be reduced by properly choosing a repumping scheme [37]. Previously we have shown that to obtain amplification without population inversion with homogeneous broadening one will have to increase the Rabi frequencies by three orders of magnitude [23,34,38]. Let us now examine how the EIT can be achieved in the presence of homogeneous and inhomogeneous broadening.…”
mentioning
confidence: 99%
See 1 more Smart Citation